Pemanfaatan Aplikasi Edmodo dalam Evaluasi Pembelajaran Bahasa Arab di Masa Pandemi Covid-19 - Hijriyatun Hijriyatun; Sutaman Sutaman; Laily Fitriani (Taqdir, 2021)
Evaluation is carried out by the teacher to find out the the level of students capabilities to absorb a lesson convey by the teacher. By evaluating the teacher can take next step in order to that learning can be done optimally. The problem arises when the pandemic requires learning to be done from home and via the internet. Evaluation must be done online too. Writing this article aims to provide an overview of how evaluation activities were carried out during the Covid 19 pandemic, especially evaluating Arabic Learning by using the Edmodo application. The research location is on Mts Negeri 1 Pasuruan. This study used qualitative exploratory research with descriptive research methods. The main data sources in this study were students of Mts Negeri 1 Pasuruan with a total of 120 respondents. Evaluation using edmodo is one solution for Arabic Teachers in evaluating Arabic learning using digital technology, especially during the COVID-1 pandemic. The results of this study explain that evaluation using Edmodo makes it easier for teachers to monitor the learning outcomes received by students in learning Arabic. Keywords: Evaluation of Learning Arabic, E Learning, Edmodo, Covid Pandemic 19